Validation of the short forms of the incontinence impact questionnaire (IIQ-7) and the urogenital distress inventory (UDI-6) in a Turkish Population - AY, NADİYE PINAR (WILEY-LISS, 2007)
Aim: To validate the Turkish versions of the IIQ-7 and UDI-6 for use in Turkish-speaking populations. Methods: After establishing the test-retest reliability and internal consistency in a pilot study, 302 patients were enrolled in the study and general and subscale scores of the questionnaires were calculated. All participants underwent an urodynamic assessment. Results: Both instruments showed a high internal consistency (Cronbach's alpha for the IIQ-7 and UDI-6 was 0.87 and 0.74, respectively) and test-retest reliability (Spearman's rho was 0.99 for both of the scales (P < 0.001). 55.6% of the participants showed urodynamic abnormality and/or leakage. 39.7% had urodynamic stress incontinence (USI) and 15.9% had detrussor overactivity (DOA) +/- USI. The mean scores of each IIQ-7 and UDI-6 were significantly higher in the USI, and DOA USI groups compared with normal women. Women with DOA +/- USI scored highest in the IIQ-7 and UDI-6. The irritative subscale scores of the 1st and 2nd items of the UDI-6 were significantly higher in the DOA USI group. The stress subscale scores of 3rd and 4th items of UDI-6 were significantly higher in the USI group. Women with postvoid residual (PVR) urine values greater than 50 ml had significantly higher obstructive subscale scores compared to the ones who had less residual volumes. Conclusions: The Turkish translated versions of the IIQ-7 and UDI-6 are reliable, consistent and valid instruments for assessing symptom severity and the impact on QOL in Turkish speaking women with urinary incontinence.
Keywords: urinary incontinence; quality of life; urodynamics; QUALITY-OF-LIFE; URINARY-INCONTINENCE; WOMEN